The Use of the Cocomelon YouTube Channel as a Medium for Introducing Children's English Vocabulary - Putri Puspa Anggraini; Nur Azizah Apriliani; Izzah Supeni; Ciptro Handrianto (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2022)
YouTube is a video-watching application that is very popular in today's society. Therefore, people can access YouTube anywhere and anytime. Not only ordinary videos, but nowadays, YouTube is also used for academic purposes for children. Children can also learn English by watching stories, music, or YouTube videos. Various videos on YouTube can be helpful. Be accessed easily, one of which is through the Cocomelon Channel. This study aims to explain using the Cocomelon YouTube channel as a learning medium for vocabulary recognition for children aged 6-12 years. This research is a case study with a qualitative method in which the researchers take observation and interview as the data collection technique. The participants in this study were children aged 6 to 12 years. From the children's feedback and interviews with parents, the result shows that using Cocomelon's YouTube channel can affect the addition of new vocabulary for children.